Bovine Brain: An in vitro Translational Model in Developmental Neuroscience and Neurodegenerative Research - Peruffo, Antonella; Cozzi, Bruno (Frontiers in Pediatrics, 2014)
Animal models provide convenient and clinically relevant tools in the research on neurodegenerative diseases. Studies on developmental disorders extensively rely on the use of laboratory rodents. The present mini-review proposes an alternative translational model, based on the use of fetal bovine brain tissue. The bovine (Bos taurus) possesses a large and highly gyrencephalic brain and the long gestation period (41 weeks) is comparable to the human pregnancy (38-40 weeks). Primary cultures obtained from fetal bovine brain constitute a validated in vitro model that allows examinations of neurons and/or glial cells under controlled and reproducible conditions. Physiological processes can be also studied on cultured bovine neural cells incubated with specific substrates or by electrically coupled electrolyte-oxide-semiconductor capacitors that permit direct recording from neuronal cells. Bovine neural cells and specific in vitro cell culture could be an alternative in comparative neuroscience and in neurodegenerative research, useful for studying development of normal and altered circuitry in a long gestation mammalian species. Use of bovine tissues would promote a substantial reduction in the use of laboratory animals.